2017
DOI: 10.1101/129007
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of Animal Behavioral Strategies by Inverse Reinforcement Learning

Abstract: Animals are able to flexibly adapt to new environments by controlling different behavioral patterns. Identification of the behavioral strategy used for this control is important for understanding animals' decision-making, but methods available for quantifying such behavioral strategies have not been fully established. In this study, we developed an inverse reinforcement-learning (IRL) framework to identify an animal's behavioral strategy from behavioral time-series data. As a particular target, we applied this… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…By contrast, the sub-circuits mediating shallow turns and omega turns were less defined (Figures 4F and S7B), suggesting that other classifications of turns might be needed to fully elucidate their underlying circuitry as some possibilities have been previously proposed (Broekmans et al, 2016; Kim et al, 2011). Also, non-rule based classifications of behaviors (Brown et al, 2013; Yamaguchi et al, 2018), especially the description of the state of the animal in shape space (Stephens et al, 2008), are reported to be successful in assessing the impact of cell-ablations (Hums et al, 2016; Yan et al, 2017) and might enable the definition of further sub-circuits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the sub-circuits mediating shallow turns and omega turns were less defined (Figures 4F and S7B), suggesting that other classifications of turns might be needed to fully elucidate their underlying circuitry as some possibilities have been previously proposed (Broekmans et al, 2016; Kim et al, 2011). Also, non-rule based classifications of behaviors (Brown et al, 2013; Yamaguchi et al, 2018), especially the description of the state of the animal in shape space (Stephens et al, 2008), are reported to be successful in assessing the impact of cell-ablations (Hums et al, 2016; Yan et al, 2017) and might enable the definition of further sub-circuits.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral recordings were performed using a Multi-Worm Tracker (Swierczek et al, 2011; Yamaguchi et al, 2018) with a CMOS sensor Camera Link Camera (8 bits, 4,096 × 3,072 pixels; CSC12M25BMP19-01B, Toshiba-Teli), a lens adaptor (F-TAR2), a Line-Scan Lens (35mm, f/2.8; YF3528, PENTAX), and a PCIe-1433 camera-link frame grabber (781169-01, National Instruments). The camera was mounted at a distance above the assay plate resulting in an image with 33.2 μm per pixel.…”
Section: Methodsmentioning
confidence: 99%
“…Once this reward function has been learnt, the model can then be used to reproduce behaviour similar to that of the system being modelled. This has been successfully applied to thermotactic behaviour in Caenorhabditis elegans [ 113 ] (electronic supplementary material, S4.8) and is likely to be applicable to other homeostatic behaviours such as feeding. Applying inverse reinforcement learning to neuronal firing data from modern imaging techniques [ 114 ] could provide a natural interpretation of the inferred reward function and way to integrate results such as the negative valence of AGRP neuronal activation [ 115 ].…”
Section: The Importance Of Stochastic Behavioural Models For Precisiomentioning
confidence: 99%